“Burning Money” By E-Commerce Platform Businesses And The Relationship With Selling Loss Based On Business Competition Law In Indonesia - Jozu Kenjiro Samudra; Sudaryat Sudaryat; Helza Nova Lita (Unram Law Review, 2022)
"Burning money" is one of the marketing strategies carried out by the perpetrator’s e-commerce platform in effort to introduce products on the internet and change the habit consumer. Cut programpricelarge on current e-commerce platformsthispopular in societyis one _shapeof "burning money". This program is done in a period of time particular with the objective of interesting the number of customers and achieving high traffic. The existence of “burning money” activity has worries that willcausesomethingcompetitionbusiness not healthy . Piecegreat price _from one _the form of "burning money" is suspectedrelatedwith predatory pricing orselllos. Methodstudyis normative juridical normative research using _regulationlegislation, theorylaw, and the opinion of scholarsrelated to law competitionbusiness and e-commerce. Data will then analyzedwithmetho descriptive analysis _symptom particular in detail, detail, and systematic. There are four aspects that are used for the study of "burning money" by using a massive price-cutting program based on Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition and related laws and regulations. As a result , the cut programthe price made by the perpetratore-commerce platform business haspotencycausecompetitionbusinessnohealthywillbutthe impact of the perpetratore-commerce platform business helppublic switch to the digital age throughe-commerce services .